CASH BUDGET FUND IMPLEMENTATION IN CALLAO MICRO-COMPANIES IN 2013 - Torre Padilla, Abdías Amando (2015)
The cash budget fund has a fundamental role in im-proving the economic capacity in micro enterprises from Callao. In light of the changes that are compli-cated and fast; at present, the management of Micro and Small Enterprises (MYPE) are facing a challenge caused by problems that arise from an empirical ma-nagement -and therefore ineffective- since it does not take into account the planning that is reflected in little to non-profitability. Therefore, to help overcome the problem previously mentioned, we stated this goal: applying the cash budget fund to improve the econo-mic capacity of Callao micro-enterprises. Therefore, in our work was concluded that through this financial tool it will start on the path of improving their economic capacity; and for this, the cash budget fund is proposed as a practical management model that contributes to the economic performance of the micro-companies.